(3cTa GddKGe Yf CSFdI GdEeGes - (3MSjf Hf eMeO GdeMdj GdTGaYj,J (B1170 (3g` s ((3ZHQGgje Hf GdMGL YTQi Gdefhai GdTGaYi s)
(3ChdgG (B:s
[ (3MeOkG (B] (3def habg ai GdOjf ef EQJVGg ef YHGOg (B[ (3CeG HYO (B] (3deG cKQ GdSDGd Yf hbGFY GdCMhGd CQOJ Cf CLeY eG jQJGM Hg GddHjH s
(3BNQgG (B:s
(3hgPG BNQ eG CQOJ LeYg , hLYdg Gddg NGdUkG dhLgg GdcQje s
(3GdfSNI HgG MhGTs
(3HGdfSNI BKGQ CQVIs
(3YdjgG JedcGJ CbOegG SfI (B1280 (3g` HZSe Ydhi Hf CMeO GdSbGas
(3cJHJ YfGhjjf GdcJH hQDhS GdaQhY HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdTGaYjs